1982
DOI: 10.1007/bf01005236
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical localization of water-soluble glycoproteins, including Group 1 allergen, in pollen of ryegrass,Lolium perenne, using ferritin-labelled antibody

Abstract: The cellular sites of the glycoproteins Group 1 allergen (glycoprotein 1) and Antigen A (glycoprotein 2) in mature ryegrass pollen have been investigated by immunoelectron microscopy. Radioimmunoassays confirm previous findings of cross-reactivity between the purified glycoprotein antigens at the high immunoglobulin G (IgG) concentrations used for localization. Freeze-drying of anthers followed by anhydrous processing has been employed because of the water solubility and mobility of the glycoproteins. A double… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Here as in all other fields of cell biology, colloidal gold has replaced ferritin [7, 18] as an electron–dense marker.…”
Section: Anhydrous Fixation: a Major Requirement To Trace Pollen Allementioning
confidence: 99%
See 1 more Smart Citation
“…Here as in all other fields of cell biology, colloidal gold has replaced ferritin [7, 18] as an electron–dense marker.…”
Section: Anhydrous Fixation: a Major Requirement To Trace Pollen Allementioning
confidence: 99%
“…Thus, alternative preparation techniques had to be developed. Grass pollen grains were fixed in absolute methanol [5] or a combination of freezing techniques and direct embedding into plastic was used [6, 7] thus avoiding aqueous fixatives and graded ethanol series. These studies localized pollen antigens and allergens in the wall and occasionally in the cytoplasm of the pollen grains.…”
Section: Introductionmentioning
confidence: 99%
“…However, they have yet to be found in orbicules of many other clinically important species, including grasses. In Lolium perenne L., Vithanage et al (1982) found group 1 allergens in the orbicules, but no labelling was obtained by Taylor et al (1994) using monoclonal antibodies. Therefore, it is still unknown whether orbicules are always loaded with allergens and which pollen allergens, i.e., major and/or minor allergens they contain.…”
Section: Discussionmentioning
confidence: 99%
“…Classical methods for localizing allergens in pollen with the help of LM are based on immunofluorescence techniques (Takahashi et al, 1989;Vithanage et al, 1982;Howlett et al, 1981;Knox et al, 1970;Belin and Rowley, 1971). Because these techniques can mask the presence of antigens in the pollen cell wall owing to autofluorescence (Knox et al, 1970), we used immunogold-silver enhancement, which has the advantages of indirect immunolabeling originally developed for TEM and makes it possible to visualize gold particles by light microscopy due to the formation of a silver precipitate (Danscher and Norgaard, 1983).…”
Section: (J Hisrochem Cytochem 46951-158 19%)mentioning
confidence: 99%